The First Experience of Aortic Valve Repeated Replacement Using the “Valve in Valve” Technique in a Patient With Dysfunction of a Biological Prosthesis - V. V. Vladimirov; L. S. Kokov; A. I. Kovalyov; S. S. Niyazov; M. V. Parkhomenko; A. V. Redkoborody; N. V. Rubtsov; N. M. Bikbova; R. Sh. Muslimov (Неотложная медицинская помощь)
Introduction. Aortic valve replacement in cardiopulmonary bypass with suture fixation of the prosthesis is the “gold standard” in cardiac surgery. Currently, the frequency of use of heart valve bioprostheses is increasing in older patients. Despite all the advantages of using heart valve bioprostheses, this type of prosthesis has a major drawback - it is not durable. In most cases, the reason for the dysfunction of prostheses in the late postoperative period is early calcification of the prosthesis valves or their rupture due to degeneration. With the development of new “gentle” techniques for replacing heart valves, transcatheter aortic valve implantation was introduced into clinical practice. The use of transcatheter aortic valve implantation (TAVI) “valve in valve” for reoperations in older patients is of great interest, since in recent years the procedure has been widely used in clinical practice and shows promising data in patients with high surgical risk.Aim of study. Show first experience of using a technique «valve in valve» at N.V. Sklifosovsky Research Institute for Emergency Medicine.Material and methods. The results of surgical treatment of a patient with aortic valve bioprosthesis dysfunction using the TAVI “valve in valve” technique are presented.Results. The use of the TAVI “valve in valve” method made it possible to perform reprosthetics of the aortic valve (AV) from a transfemoral approach, not to increase the volume of intervention during reoperation, to avoid trauma to the structures of the heart and nearby tissues when accessing the AV in a patient with a high surgical risk.Conclusion. The use of the TAVI “valve in valve” method in cardiac surgery makes it possible to achieve good immediate and long-term results when it is necessary to replace the AV in patients with a high surgical risk.